Moving to Opportunity in Boston: Early Results of a Randomized Mobility Experiment - Katz, L. F.; Kling, J. R.; Liebman, J. B. (Quarterly Journal of Economics, 2001)
We examine short-run impacts of changes in residential neighborhoods on the well-being of families residing in high-poverty public housing projects who received Section 8 housing vouchers through a random lottery. Households offered vouchers experienced improvements in multiple measures of well-being relative to a control group, including increased safety, improved health among household heads, and fewer behavior problems among boys. There were no significant short-run impacts of vouchers on the employment, earnings, or welfare receipt of household heads. Children in households offered vouchers valid only in low poverty neighborhoods also had reduced likelihood of injuries, asthma attacks, and victimizations by crime.